REACTION AGGLUTINATION OF SESAME SEED EXTRACT (Sesamum indicum L.) TEST IN BLOOD GROUP O - yeni avidhatul husnah (Jurnal Labora Medika, 2019)
Blood type O has no antigens blood cells, but can produce antibodies against antigens A and B. Detection of blood group O antigen is currently based on the presence of H. Examination with anti-H was found from seed lectin Ulex, Ulex while living only in subtropical areas. Sesame is a member of Family Pedaliaceae thrives in the tropics. This study aims to obtain anti-O derived from biological sources Indonesia and determine the effect on a sesame seed extract agglutination reaction with blood group O. The research was conducted by the method of manufacture of dry sesame seed extract that has been done dilution with solvent concentration ratio is 1:2; 1:10, and 1:100 supernatant were subsequently taken. In making Ulex seed extract with a concentration of 1:10, further testing on the blood group of each seed extract concentration. Based on the research that has been done, the result that sesame seed extract is able to lyse erythrocytes in the blood group A, B, and O concentration ratio for all treatments and did not reveal any agglutination reaction in all treatments. Meanwhile, the Ulex europaeus seed extract can mengagglutinasi erythrocytes in blood type O. It can be concluded that the extract of sesame seeds can not be used as an anti-H replaces Ulex seeds, sesame seeds but potentially as an agent of hemolysis.